3-dimensional Brain-computer Interface Control through Simultaneous Overt Spatial Attentional and Motor Imagery Tasks - Meng, Jianjun (IEEE Trans Biomed Eng, 2018)
OBJECTIVE: While noninvasive electroencephalography (EEG) based brain-computer interfacing (BCI) has been successfully demonstrated in two-dimensional (2D) control tasks, little work has been published regarding its extension to practical three-dimensional (3D) control. METHODS: In this study, we developed a new BCI approach for 3D control by combining a novel form of endogenous visuospatial attentional modulation, defined as overt spatial attention (OSA), and motor imagery (MI). RESULTS: OSA modulation was shown to provide comparable control to conventional MI modulation in both oneand two- dimensional tasks. Furthermore, this work provides evidence for the functional independence of traditional MI and OSA, as well as an investigation into the simultaneous use of both. Using this newly proposed BCI paradigm, sixteen participants successfully completed a 3D eight target control task. Nine of these subjects further demonstrated robust 3D control in a twelve target task, significantly outperforming the information transfer rate achieved in the 1D and 2D control task (29.7±1.6 bits/min). CONCLUSION: These results strongly support the hypothesis that noninvasive EEG based BCI can provide robust 3D control through endogenous neural modulation in broader populations with limited training.